Semiempirical and Ab Initio calculation of the molecular structures of substituted N-Benzoylimidazoles - Paulo Meneghelli (Semina: Ciências Exatas e Tecnológicas, 2001)
Possible reasons of low reactivities of some N-(2-X-benzoyl) imidazoles utilising ab initio Hartree-Fock calculations have been studied in imidazole-catalyzed hydrolysis. The elucidation of its molecular structures display that the inhibition of resonance, between the carbonyl group and the aromatic moiety, due to steric effects are very much important than that a possible stabilization of the reactant state by a donor-acceptor effects interaction between the orto nitro group of benzene ring and the imidazole ring.